The impact of radiation-related lymphocyte recovery on the prognosis of locally advanced esophageal squamous cell carcinoma patients: a retrospective analysis - Hongshan Ji; Ping Zhang; Chanjun Zhen; Liyuan Fu; Dongjie Lv; Wenwen Bai; Rui Zhang; Jing Li; Hang Gao; Yajing Wang; Qiuying An; Yuhao Su; et al. (Radiation Oncology)
Abstract Background The impact of radiation-related lymphocyte recovery on prognosis in locally advanced esophageal squamous cell carcinoma (LA-ESCC) remains unclear. Methods Patients with stage II-IVa ESCC who received definitive RT were screened. Collect absolute lymphocyte counts (ALCs) before, during, and after RT. The recovery status of lymphocytes was observed at one-month post-RT (P1) and three months post-RT (P3). Patients with relatively lower lymphocyte recovery levels at P1 were divided into Group a and those with higher levels were divided into Group b. Patients with relatively lower lymphocyte recovery levels at P3 were divided into Group A and those higher were divided into Group B. Kaplan-Merier’s analysis and Cox analysis were conducted to compare survival outcomes. Binary logistic regression analyses was employed to ascertain factors associated with lymphocyte recovery. Results 116 patients were enrolled. During RT, ALCs reached the bottom 5 weeks after RT started and 70.7% of patients experienced G3 lymphopenia. The median OS for Group a and Group b were 38.1 months and 14.4 months, p = 0.097. The median PFS for Group a and Group b were 14.2 months and 10.0 months, p = 0.037. Whereas, the median OS for Group A and Group B was 14.5 months and 22.2 months, p = 0.019. The median PFS for Group A and Group B were 8.4 months and 12.4 months, p = 0.021. Cox multivariable analysis revealed that higher lymphocyte recovery level at P3 was significantly associated with superior OS (p = 0.040, HR0.636) and PFS (p = 0.028, HR0.627). The logistic analysis identified a positive association between G4 lymphopenia during RT (p = 0.012, OR 7.742) and PTV dose < 60 Gy (p = 0.014, OR 2.655) with lymphocyte recovery. Conclusions The prognostic value of lymphocyte recovery status at P3 appears to be greater than that of lymphocyte recovery status at P1 for locally advanced ESCC patients. Radiation-related lymphocyte recovery might serve as a valuable prognostic factor in LA-ESCC.